UZLUKSIZ KASBIY RIVOJLANTIRISH JARAYONIDA ZAMONAVIY RAHBARLARNING BOSHQARUV KOMPETENSIYALARINI RIVOJLANTIRISH - Bahriddinova Gulruh Farhod qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article presents thoughts and opinions about the management competencies of modern leaders and the stages of its development and development features, analysis of the situation, decision-making, goal setting, and organization of activities in order to achieve results.